MULTISCALE EXPERIMENTAL AND THEORETICAL STUDY ON MECHANOBIOLOGY AND HOMEOSTASIS OF TUMORS - Gerasimova-Chechkina, E.I.; Nikitiuk, A.S.; Lyapunova, E.A.; Gileva, O.S.; Naimark, O.B. (Perm Federal Research Centre Journal, 2017)
We considered multifractality as a characteristic of biological systems in normal state while monofractality as a sign of its tumor transformation based on the theoretical information about the development of cell and tissue damage in biological structures and on the investigations of spatio- temporal fluctuations of phase thicknesses (coherent phase microscopy data of cells) and temperature (infrared thermography data of women’s breasts).